MORBIDITY AND MORTALITY FROM CARDIOVASCULAR DISEASES ACCORDING TO THE SEA-LEVEL RELATED ALTITUDE OF A REGION - A. A. Dotdaeva; Kh. A. Kurdanov; S. A. Boytsov (Кардиоваскулярная терапия и профилактика)
It is known that the common risk factors (RF) of cardiovascular diseases (CVD) do exist and do influence all people the same. Among them are arterial hypertension, smoking, total cholesterol, obesity etc. However there are specifics of RF realization connected to climatogeographic specifics, i.e. high mountain altitudes. The review is concerned on the influence of the high altitude influence on RF of CVD. Some papers show that in high altitudes inhabitants the RF of CVD were prognostically malevolent, but the level of total and coronary mortality was lower in mountain inhabitants that can be explained by more intensive physical exertion with the background moderate hypoxia. There is an opinion that lower mortality in higher altitudes can be explained as connected with physiological adaptation to altitude and/or specifics of the climate (i.e. with UV-rays exposure, those become more intensive by 10% every 300 m). Lipidogramm are supposedly linked to moderate hypoxia and lowering of temperature, also the diet specifics might influence. However there is no stabile relation of mortality and the parameters studied. So the results collected in different trials are still controversial. But if long-term living in higher altitudes, secondarily, by the activation of adaptation capacities of the body, diet specifics and physical exertion, leads to the decrease of morbidity and mortality from CVD, short-term visiting of the mountains might be harmful for some persons and this requires individualized approach to recommendations of prevention.